The Non-Governmental Organization (Ngo)/Community Organization (Co) Existence And The Likelihood Of The Local Conflicts: Evidence From Aceh Province - Sandhita, Randa (The Islamic Education and Multiculturalism Foundation, 2023)
Aceh officially entered a post-conflict era in 2005, in its part of post-conflict peace development, the Local Conflict still escalated between citizens, between villages, between Ethnic, with local government, with the local security force, and between students and other group conflicts. This study examines the association of the Non-Governmental Organization (NGO)/Community Organization (CO)’s to chance of having local conflict in village in Aceh. we use the data of the Indonesian village survey (Potensi Desa/Podes) in 2008, 2011, 2014, and 2018 from statistics Indonesia, and supported with interview results with 20 village leaders. We use Binary Logit to quantify the association between NGO/CO existence and the chance of likelihood of the local conflict. Our results show that the presence of NGO/CO within the village increases the chance of the likelihood of local conflict. And if there is an interaction between NGO/CO and BPD within the village, the presence of NGO/CO is decreasing the chance of likelihood of local conflict in Aceh.